1996
DOI: 10.1056/nejm199612123352401
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pamidronate in Reducing Skeletal Complications in Patients with Breast Cancer and Lytic Bone Metastases

Abstract: Monthly infusions of pamidronate as a supplement to chemotherapy can protect against skeletal complications in women with stage IV breast cancer who have osteolytic bone metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
450
2
19

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 944 publications
(488 citation statements)
references
References 23 publications
11
450
2
19
Order By: Relevance
“…Despite antiresorptive therapy, repair of existing lesions is not seen, and progressive disease is associated with new skeletal events. (8)(9)(10)(11)(12)(13) New strategies to reduce skeletal-related events and improve patient outcome are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Despite antiresorptive therapy, repair of existing lesions is not seen, and progressive disease is associated with new skeletal events. (8)(9)(10)(11)(12)(13) New strategies to reduce skeletal-related events and improve patient outcome are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Medical therapies include systemic chemotherapy/hormonal therapy and medications specific for spinal metastases, such as steroids, analgesics, and bisphosphonates [6,12,31,34,41]. Bisphosphonates are highly effective in reducing bone pain, hypercalcemia and pathological fractures, and they are frequently used at our institutions [23,30,31]. For patients with localized bone pain that has not responded to systemic therapy and analgesics, external beam irradiation (30 Gy in ten fractions) is the treatment of choice and usually provides good pain relief [29,31,32,40].…”
Section: Discussionmentioning
confidence: 99%
“…The bisphosphonates, notably intravenous pamidronate (Purohit survival of 2.1 years et al, 1994;Conte et al, 1996;Hortobagyi et al, 1996) and to a lesser 0.001, Figure 5). This extent oral clodronate (Paterson et al, 1993), have been shown to patients subsequently relieve pain, reduce analgesic consumption and improve mobility.…”
Section: Discussion Chi= 1918mentioning
confidence: 99%
“…Support for such selection does however require analysis of a larger database of patients, with recording of skeletal events and their subsequent treatment. It is hoped that the recent randomized trials of pamidronate (Hortobagyi et al, 1996;Lipton et al, 1997), which included the collection of data for economic evaluation as well as meticulous recording of skeletal events, will use these data for analysis not only by treatment group but also according to prognostic factors, including those identified in this study, to assess whether the selective use of bisphosphonates improves the cost-effectiveness of this new treatment modality. In addition, and possibly of greater value, might be the ability to specify those patients at most risk of developing serious complications of bone metastases, particularly pathological fracture and hypercalcaemia, but the relevant predictors remain to be identified.…”
Section: Discussion Chi= 1918mentioning
confidence: 99%